2020
DOI: 10.32604/cmes.2020.011067
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics Analysis of Ice-Adhesion Transmission Tower-Line System under Effect of Wind-Induced Ice Shedding

Abstract: The tower line system will be in an unsafe status due to uniform or uneven fall of ice coating which is attached to the surface of tower and lines. The fall of ice could be caused by wind action or thermal force. In order to study the dynamic characteristics of the self-failure of the transmission line under the action of dynamic wind load, a finite element model of the two-span transmission tower line system was established. The birth and death element methods are used to simulate the icing and shedding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Generally, wind speed is inversely proportional to temperature, as reflected in the icing thickness of a bare conductor [105], even resulting in the line galloping [106,107]. Yu et al [108] found that ice shedding occurred on the 20 mm icing film of a conductor (ground) wire in the first 20 s at wind speeds of 15 m/s. In addition, Kermani et al [106] simulated the fracture behavior of atmospheric ice on bare conductors under different wind speeds and found it sometimes occurred during line galloping when stresses arose at a wind speed of 5 m/s.…”
Section: Icing Formsmentioning
confidence: 99%
“…Generally, wind speed is inversely proportional to temperature, as reflected in the icing thickness of a bare conductor [105], even resulting in the line galloping [106,107]. Yu et al [108] found that ice shedding occurred on the 20 mm icing film of a conductor (ground) wire in the first 20 s at wind speeds of 15 m/s. In addition, Kermani et al [106] simulated the fracture behavior of atmospheric ice on bare conductors under different wind speeds and found it sometimes occurred during line galloping when stresses arose at a wind speed of 5 m/s.…”
Section: Icing Formsmentioning
confidence: 99%
“…ANSYS‐based finite element simulation model of the overhead line can reflect the load in the natural line [24, 25]. A 10 kV transmission line finite element simulation model is established to evaluate the effectiveness of the method.…”
Section: Simulation Verificationmentioning
confidence: 99%
“…Transmission tower is an important type of infrastructure for power transmission, and its safety is directly related to operation of the power system [1]. For example, Typhoon Pigeon attacked the Zhuhai area in China in August 2017, resulting in collapse of a transmission tower at the sea eight A line, so power outages were suffered [2].…”
Section: Introductionmentioning
confidence: 99%